Profit tax with holdings and firms' compliance behavior in Ecuador. - Rivadeneira Álava, Ana Mercedes (2010)
This investigation analyzes Ecuadorian firms’ compliance behavior. Using firm-level data from the Tax Administration Agency in Ecuador (SRI), we compute the distribution of firms’ 2006 profit-tax/income ratio (tax-burden) and show the existence of obvious spikes just around the firms’ withholding requirements. While the theory suggests that tax evasion or tax avoidance could explain these patterns, one cannot rule out other explanations.